2015
DOI: 10.1038/hr.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of autophagy by atorvastatin via Akt/mTOR pathway in spontaneously hypertensive rats

Abstract: Autophagy is activated in hypertension-induced cardiac hypertrophy. However, the mechanisms and significance of an activated autophagy are not clear. This study was designed to determine the role of atorvastatin (ATO) in cardiac autophagy and associated benefits on cardiac remodeling and left ventricular function in spontaneously hypertensive rats (SHRs). Twenty-eight male SHRs at 8 weeks of age were randomized to treatment with vehicle (saline solution; SHR+V) or ATO (SHR+ATO; 50 mg kg(-1) per day) for 6 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
(82 reference statements)
2
22
0
Order By: Relevance
“…Our study results showed that atorvastatin treatment markedly reduced cell viability compared to untreated NIT-1 cells through increasing PARP1 activation and subsequently inducing necrosis and autophagy induction. This finding confirms previous findings that atorvastatin induced autophagic activity in vivo and in vitro [3740]. In 2012, Lim et al demonstrated that pravastatin can improve renal function in CsA-induced autophagic cell death through reducing LC3-II and P62 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Our study results showed that atorvastatin treatment markedly reduced cell viability compared to untreated NIT-1 cells through increasing PARP1 activation and subsequently inducing necrosis and autophagy induction. This finding confirms previous findings that atorvastatin induced autophagic activity in vivo and in vitro [3740]. In 2012, Lim et al demonstrated that pravastatin can improve renal function in CsA-induced autophagic cell death through reducing LC3-II and P62 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, LC3 and the ratio of LC3-II/LC3-I are considered markers of autophagy. Autophagosomes can be observed using a transmission electron microscope and are considered “gold standards” in terms of morphological/ultrastructural evidence of autophagy activation, [13] while upregulation of p62 poses as a marker of autophagosomal clearance [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…When cells are exposed to certain internal and external environment stimuli such as nutritional stress or invasion by microbial or viral pathogens, increased autophagy is induced to maintain cell survival [1,3]. Autophagy also plays a crucial mediating role in the development of various pathologies in humans, including neurodegeneration [4], tumor formation [5,6], and cardiovascular disease [7].…”
Section: Introductionmentioning
confidence: 99%